Stress Distribution between Bonding Surface of Dental Filling in Enamel and Dentine - Soliheen, M.; Kurniawan, Denni; Nor, F. (2015)
© 2015 Dental decay (or caries) is common disease worldwide. A solution for this is by having dental filling. This study intends to investigate the stress magnitude and distribution when two types of dental filling materials (i.e., amalgam and porcelain) are used. Two scenarios, when the filling covers only the enamel and when it covers both the enamel and dentine regions are compared. Finite element analysis was used to for this purpose on an arbitrarily shaped dental filling inserted on a tooth loaded by a pressure. It was found that the scenario when dental filling covers both enamel and dentine is preferred in terms of stress magnitude and distribution, for both amalgam and porcelain.